WORKERS LEGAL PROTECTION IMPLEMENTATION WITH A SPECIFIC TIME WORK AGREEMENT AT GRAFITECINDO CIPTA PRIMA COMPANY - Fahmi, Heril; Sidiq, Jaelani (IBLAM LAW REVIEW, 2021)
Implementation of PKWT according to Law no. 13 of 2003 concerning Manpower states that the PKWT work relationship requires a written agreement in Indonesian and may not be for permanent work in the company which, if violated, will result in changing the work relationship to PKWTT. Likewise with the rights to wages, working time and employee participation in the BPJS. Meanwhile, the terms of work are regulated in a Work Agreement or Collective Bargaining Agreement. Workers Union at PT. GCP, namely GSPMII, has succeeded in overseeing the implementation of PKWT in the form of fulfilling work norms and conditions for PKWT workers in companies and also guaranteeing continuity to work at the company. Although there are still violations where the sanctions for violating the PKWT mechanism, namely changing the status to PKWTT, cannot be implemented so that there is a work agreement that always continues, but in the mind of the labor union, it is a solution to guarantee the continuity of work for PKWT workers in the company. This study limits the discussion to the problem of implementing PKWT at PT. GCP is in accordance with Law Number 13 of 2003 concerning Manpower and how the role of PUK GSPMII PT. GCP in overseeing the fulfillment of work norms and conditions and providing guarantees for the continuity of employment of contract workers in the company. This thesis research uses the empirical normative legal method where the authors conduct research on the application of labor law at PT. Grafitecindo Ciptaprima, where the researcher is in charge of the trade union. Employers must comply with the legal rules regarding the PKWT mechanism, including the fulfillment of temporary work norms and conditions for trade unions must have a good understanding and strategy in dealing with the problem of violating the PKWT mechanism, not only prioritizing legal certainty but also but also it would be better if it prioritizes the principles benefit, especially for workers.